رضا طلبة الدراسات العليا عن جودة الخدمات التعليمية (دراسة ميدانية على طلبة الدراسات العليا في كلية الآداب بجامعة تشرين) - زاهر, بسام; جنبلاط, مادلين (Latakia University Journal - Economic and Legal Sciences Series, 2019)
The aim of this study is to identify the quality of educational services offered by the Faculty of Arts at Tishreen University from the point of view of postgraduate students and to determine the level of students' satisfaction with the educational services provided. The researcher used the descriptive method to measure students' satisfaction with the quality of educational services offered by the Faculty of Arts at Tishreen University. A questionnaire was designed and distributed to postgraduate students in order to measure the quality of educational services in Tishreen University. Spss. After analyzing the data, the quality of the educational services provided by the Faculty of Arts at Tishreen University was not found in the perspective of postgraduate students according to the dimensions of quality of health services (concrete, dependability, response, empathy, trust and safety). هدفت هذه الدراسة إلى التعرف على جودة الخدمات التعليمية المقدمة في كلية الآداب في جامعة تشرين من وجهة نظر طلبة الدراسات العليا، ومعرفة درجة رضى الطلبة عن الخدمات التعليمية المقدمة. تكون مجتمع الدراسة من طلبة الدراسات العليا في كلية الآداب في جامعة تشرين. استخدمت الباحثة المنهج الوصفي لقياس رضى الطلبة عن جودة الخدمات التعليمية المقدمة في كلية الآداب في جامعة تشرين، وتم تصميم وتوزيع استبانة على طلبة الدراسات العليا من الخدمات التعليمية المقدمة بغية قياس درجة جودة الخدمات التعليمية في جامعة تشرين، كما تم دراسة و تحليل البيانات باستخدام برنامج SPSS ، وبعد تحليل البيانات تبين انخفاض درجة توافر جودة الخدمات التعليمية المقدمة في كلية الآداب في جامعة تشرين من وجهة نظر طلبة الدراسات العليا وفقا لأبعاد جودة الخدمة التعليمية(الملموسية،الاعتمادية، الاستجابة،التعاطف ،الثقة والأمان).